Privacy and democracy. Issue 3 (2nd September 2016) - Voice, Paul
Abstract : The meaning of privacy has been frequently disputed in the philosophical and legal literature since Warren and Brandeis first argued for it as a distinct and important personal and social value. Nevertheless, while the meaning of privacy is held to be vague, there is general agreement that Warren and Brandeis were correct in their assessment of its value. Theorists of democracy, on the other hand, have been ambivalent towards the realm of the private. This paper interrogates the intersection between privacy and democracy, questioning the place of privacy as a distinctly democratic value.